Pengaruh Penggunaan Media Congklak Terhadap Kemampuan Berhitung Siswa Kelas II SDN 165 Palembang - Maharani Maharani; Nuranisa Nuranisa (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
This research is motivated by the low arithmetic ability of grade II elementary school student, especially in arithmetic material. This study aims to determine the effect of using congklak media on the arithmetic ability of grade II student of SDN 165 Palembang. The method used is Quasi Experimental Design with Nonequivalent Control Group Design. The sample consists of two classes, namely class II A and II B, experimental class II B which uses congklak media and control class II A with conventional methods. The research instrument is a multiple-choice test that has been validated. The hypothesis testing produced is Significant Value (2-tailed) = 0,005 and T = 3.084 because the significant value (2-tailed) 0,005 < 0,025, it can be concluded that H_a is accepted and H_o is rejected. These result indicate a significant difference in arithmetic ability between the two classes, with the average posstest of the experimental class being higher. Thus, the use of congklak media has a positive effect on student arithmetic ability. It can be concluded that there is an effect of using congklak media on the arithmetic ability of grade II student of SDN 165 Palembang.